Vehicle Speed Control Using Gain Scheduling PID Controller - Abdul Kadir, Faizul Akmar; Hudha, Khisbullah; Mohammad Nasir, Mohd Zakaria (Trans Tech Publications, 2012)
This paper presents a control strategy for controlling speed of a vehicle experiencing the disturbance from road gradient using simulation method.A non-linear vehicle longitudinal model is used for modeling the vehicle behavior in longitudinal direction and the vehicle is subjected to several positive (uphill) road gradient disturbances.The gain scheduling Proportional-IntegralDerivative (PID) controller is proposed to achieve the control objective.MATLAB-SIMULINK is chosen as a simulation tool to simulate the vehicle dynamics behavior and evaluate the performance of the control structure.The result shows that the proposed controller is effective in controlling the vehicle speed with relatively lower speed drop.The controller performance is far better than the fixed gain PID controller.